The optimal drug adherence to maximize the efficacy and safety of non-vitamin K antagonist oral anticoagulant in real-world atrial fibrillation patients. Issue 4 (10th October 2019) - Kim, Daehoon; Yang, Pil-Sung; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Kim, Jong-Youn; Sung, Jung-Hoon; Pak, Hui-Nam; Lee, Moon-Hyoung; Lip, Gregory Y H; Joung, Boyoung
Abstract: Aims: To investigate the association between adherence to non-vitamin K antagonist oral anticoagulant (NOAC) and clinical outcomes and to determine the optimal cut-off level of NOAC adherence among patients with atrial fibrillation (AF). Methods and results: Using the Korean National Health Insurance Service database, we identified 96 197 patients with non-valvular AF who initiated NOAC or warfarin in 2013–16. We compared clinical outcomes between adherent [proportion of days covered (PDC) ≥80%] vs. non-adherent (PDC <80%) NOAC users, and further with warfarin users. We assessed the outcomes according to different levels of adherence. The proportion of adherent NOAC users was 64.0%. Compared with non-adherent NOAC users, adherent NOAC users were at lower risks of ischaemic stroke/systemic embolism (SE) [adjusted hazard ratio (aHR) 0.73, 95% confidence interval (CI) 0.69–0.79], and myocardial infarction (aHR 0.82, 95% CI 0.72–0.93), whereas there was no significant risk alteration for major bleeding (aHR 1.01, 95% CI 0.91–1.11). Compared with warfarin, non-adherent NOAC use failed to have better efficacy against ischaemic stroke/SE (aHR 0.99, 95% CI 0.93–1.05) and rather had increased risk of myocardial infarction (aHR 1.13, 95% CI 1.03–1.25). In NOAC users, the risks of adverse outcomes decreased according to gradual increase of adherence rates with the lowest risks in ≥90%, except for major bleeding in which there were no significant associations. Conclusions: In an adherence level-dependent fashion, adherent use of NOAC showed better clinical outcomes without increasing bleeding risk. Maintaining ≥90% of adherence optimizes effectiveness of NOAC therapy without compromising its safety.